Seven Tesla Evidence for Columnar and Rostral–Caudal Organization of the Human Periaqueductal Gray Response in the Absence of Threat: A Working Memory Study - Fischbach, Alexandra K.; Satpute, Ajay B.; Quigley, Karen; Kragel, Philip A.; Chen, Danlei; Bianciardi, Marta; Wald, Larry; Wager, Tor D.; Choi, Ji-Kyung; Zhang, Jiahe; Barrett, Lisa Feldman; Theriault, Jordan E. (The Journal of neuroscience, 2024)
The periaqueductal gray (PAG) is a small midbrain structure that surrounds the cerebral aqueduct, regulates brain–body communication, and is often studied for its role in “fight-or-flight” and “freezing” responses to threat. We used ultra-high-field 7 T fMRI to resolve the PAG in humans and distinguish it from the cerebral aqueduct, examining its in vivo function during a working memory task ( N = 87). Both mild and moderate cognitive demands elicited spatially similar patterns of whole-brain blood oxygenation level-dependent (BOLD) response, and moderate cognitive demand elicited widespread BOLD increases above baseline in the brainstem. Notably, these brainstem increases were not significantly greater than those in the mild demand condition, suggesting that a subthreshold brainstem BOLD increase occurred for mild cognitive demand as well. Subject-specific masks were group aligned to examine PAG response. In PAG, both mild and moderate demands elicited a well-defined response in ventrolateral PAG, a region thought to be functionally related to anticipated painful threat in humans and nonhuman animals—yet, the present task posed only the most minimal (if any) “threat,” with the cognitive tasks used being approximately as challenging as remembering a phone number. These findings suggest that the PAG may play a more general role in visceromotor regulation, even in the absence of threat.